Impact of trade liberalization on agriculture in the near East and North Africa - Minot, Nicholas; Chemingui, Mohamed Abdelbasset; Thomas, Marcelle; Dewina, Reno; Orden, David (International Food Policy Research Institute, 2007)
In the past two decades, many countries in the Near East and North Africa region have reformed the agricultural sector by lowering agricultural tariffs, liberalizing domestic prices and reducing consumer food subsidies. However, trade restrictions and domestic price support mechanisms are still prevalent for a few strategic commodities (such as wheat), and there is wide divergence among the countries in terms of the extent and depth of liberalization. Under the Euro-Mediterranean Partnership launched in 1995, ongoing and future bilateral free trade agreements between the European Union and several Arab Mediterranean countries could lead to further trade liberalization. In addition, some countries have recently signed free trade agreements with the United States of America, and more countries in the Near East and North Africa region are expected to sign bilateral trade agreements with the United States in the near future.